Baculites ovatus SAY, 1820, a North American ammonite from the Maastrichtian of Roquefort, Landes, France - Kennedy, W; Bilotte, M (2002)
Baculites ovatus, SAY, 1820, a distinctive baculite previously known only from the condensed Upper Campanian-Lower Maastrichtian phosphatic nodule bed at the base of the Navesink Formation in New Jersey, U.S.A., is described from the Maastrichtian Calcaire à Orbitoides of Roquefort, Landes, France. It adds to the growing number of Upper Campanian and Maastrichtian ammonites, many thought previously to be endemic to North America, that occur on both sides of the North Atlantic. © 2002 E. Schweizerbart'sche Verlagsbuchhandlung.